Quantitative assessment of the functional plasticity of memory CD8+ T cells. Issue 4 (12th February 2016) - Baz, Adriana; Groves, Penny; Buttigieg, Kathy; Apte, Simon H.; Kienzle, Norbert; Kelso, Anne
Abstract : Although naïve CD8 + T cells lose the ability to change cytokine profile when they differentiate into effector cells, a substantial fraction of memory cells primed in the same response display functional plasticity. Tailoring of immune function can therefore continue in the secondary response at the level of the individual memory cell. Abstract : While the functional plasticity of memory CD4 + T cells has been studied extensively, less is known about this property in memory CD8 + T cells. Here, we report the direct measurement of plasticity by paired daughter analysis of effector and memory OT‐I CD8 + T cells primed in vivo with ovalbumin. Naïve, effector, and memory OT‐I cells were isolated and activated in single‐cell culture; then, after the first division, their daughter cells were transferred to new cultures with and without IL‐4; expression of IFN‐γ and IL‐4 mRNAs was measured 5 days later in the resultant subclones. Approximately 40% of clonogenic memory CD8 + T cells were bipotential in this assay, giving rise to an IL‐4 − subclone in the absence of IL‐4 and an IL‐4 + subclone in the presence of IL‐4. The frequency of bipotential cells was lower among memory cells than naïve cells but markedly higher than among 8‐day effectors. Separation based on high or low expression of CD62L, CD122, CD127, or Ly6C did not identify a phenotypic marker of the bipotential cells. Functional plasticity in memory CD8 + T‐cell populations can therefore reflect modulation at the level of a single memory cell and its progeny.